Kreacja systemów wartości u młodzieży w sektorze fonograficznym - Tarka, Piotr; Pachnowska, Beata (Systems of Values' Creation within Youth Market in the Phonographic Industry, 2009)
The authors of the following article describe particular methods and techniques of market creation used in the phonographic industry. The principal scientific goal refers to the aspects of values creation in the youth market. It is discussed and also argued whether the success in running business and achieving goal by recording companies operating within their market depends mainly on the appeasement of customers' virtual and present needs or it is based on the stimulation of new needs. These kinds of new needs can be indirectly created by making and instilling systems of values into customers right (much more profitable from the prospect of growing music business). These values are certainly created by recording companies carrying an activity in the phonographic industry. Reasons that urge these companies and the whole business area to accept such market rules are for contemporary and dynamically changing external environment.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 259-269